HUBUNGAN SELF-OBJECTIFICATION DENGAN BODY DISSATISFACTION PADA REMAJA PEREMPUAN PENGGUNA TIKTOK - Bunga Aisya; Rinaldi Rinaldi (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Visual-based social media platforms have become an important part of adolescents’ daily lives, with TikTok emerging as one of the most frequently used applications among female teenagers. The platform exposes users to a wide range of appearance-related content, including beauty trends, edited images, and idealized body representations, which may influence how they evaluate their own physical appearance. Repeated exposure to such content can encourage self-objectification, whereby individuals prioritize external evaluations of their bodies, potentially contributing to body dissatisfaction. This study explored the relationship between self-objectification and body dissatisfaction among adolescent female TikTok users in Padang City. Using a quantitative correlational approach, data were collected from 148 participants selected through purposive quota sampling. Responses were obtained online through Google Forms using the Self-Objectification Scale and the Body Dissatisfaction Scale for Women. Pearson Product-Moment correlation analysis was employed to assess the association between the variables. The results are expected to provide empirical evidence regarding the psychological effects of social media use on adolescent girls and to contribute to a better understanding of body image development in contemporary digital environments. Furthermore, the findings may support the design of educational and preventive interventions focused on digital literacy and adolescent mental well-being. Keywords: self-objectification, body dissatisfaction, TikTok, social media, adolescent girls. ABSTRAK Penggunaan TikTok yang semakin masif di kalangan remaja perempuan memengaruhi cara individu memandang tubuhnya melalui paparan konten kecantikan, penggunaan filter digital, dan standar tubuh ideal yang tidak realistis. Kondisi tersebut berpotensi meningkatkan self-objectification, yaitu kecenderungan individu menilai tubuh berdasarkan perspektif orang lain, yang kemudian dapat memunculkan body dissatisfaction. Fokus penelitian ini adalah mengidentifikasi hubungan antara kecenderungan self-objectification dan tingkat body dissatisfaction pada remaja perempuan pengguna TikTok. Untuk mencapai tujuan tersebut, digunakan pendekatan kuantitatif dengan desain korelasi sebagai metode analisis. Data diperoleh dari 148 remaja perempuan pengguna TikTok di Kota Padang yang ditetapkan sebagai partisipan melalui teknik purposive quota sampling. Pengumpulan data dilakukan secara daring melalui Google Form dengan menggunakan instrumen Body Dissatisfaction Scale for Women dan Self-Objectification Scale. Uji korelasi Pearson Product Moment digunakan untuk menganalisis hubungan yang terjadi antara variabel penelitian. Melalui temuan yang dihasilkan, penelitian ini diharapkan dapat berkontribusi terhadap penguatan kajian psikologi perkembangan dan psikologi media digital, terutama dalam menjelaskan proses terbentuknya citra tubuh pada remaja perempuan di era media sosial visual. Selain itu, hasil penelitian diharapkan menjadi dasar bagi upaya penguatan literasi digital dan edukasi kesehatan mental guna meminimalkan dampak psikologis negatif penggunaan media sosial pada remaja.